2017
DOI: 10.1126/sciadv.1601614
|View full text |Cite
|
Sign up to set email alerts
|

Role of damping in spin Seebeck effect in yttrium iron garnet thin films

Abstract: We report an experimental study on how the spin Seebeck effect in magnetic insulators depends on damping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 47 publications
(113 reference statements)
4
35
1
Order By: Relevance
“…A gallium signature was also reported in Ref. [25], where YIG layers of 20 nm thickness were grown on GGG (111) by magnetron sputtering at room temperature followed by a few hours of annealing in oxygen at 800°C. The XPS spectra presented in Ref.…”
Section: Depth-resolved Chemical Composition Of Yig/ggg Films By supporting
confidence: 63%
See 2 more Smart Citations
“…A gallium signature was also reported in Ref. [25], where YIG layers of 20 nm thickness were grown on GGG (111) by magnetron sputtering at room temperature followed by a few hours of annealing in oxygen at 800°C. The XPS spectra presented in Ref.…”
Section: Depth-resolved Chemical Composition Of Yig/ggg Films By supporting
confidence: 63%
“…The XPS spectra presented in Ref. [25] show noticeable traces of Ga (both Auger and PE peaks) that are, however, claimed by the authors to come from the GGG substrate. This is arguable as the photoelectrons excited in the GGG substrate are not supposed to be able to escape through a 20 nm thick YIG film.…”
Section: Depth-resolved Chemical Composition Of Yig/ggg Films By mentioning
confidence: 88%
See 1 more Smart Citation
“…21 A typical setup, utilizing an out-of-plane temperature gradient and an in-plane magnetic field, has been used to investigate the ANE in previous works. [22][23][24][25][26] The trouble with this configuration is that, in addition to generating an ANE voltage, the out-of-plane temperature gradient can also generate a spin current through the so-called longitudinal spin Seebeck effect (LSSE), 22,[27][28][29][30][31][32][33] which flows directly from the ferromagnetic (FM) into the adjacent non-magnetic metal (NM) and generates a voltage because of the inverse spin Hall effect (ISHE). In order to distinguish the spin Seebeck effect (SSE) and ANE, extensive efforts [34][35][36][37] have been made to compare the voltage in different temperature gradient configurations.…”
mentioning
confidence: 99%
“…Even the amplification of propagating dipolar magnons by a thermal spin-transfer torque created by spin currents, which are generated through the spin Seebeck effect (SSE), was reported [158]. Recently, the role of a damping in the spin Seebeck effect in yttrium iron garnet thin films was studied experimentally [159]. It was demonstrated that a decrease in the intrinsic damping of the magnetic material gives rise to an increase in the SSE coefficient, and this response also shows a quasilinear behavior.…”
Section: Magnon Caloritronicsmentioning
confidence: 99%